MODEL PENENTUAN HARGA SAHAM: PENGUJIAN CAPITAL ASSET PRICING MODEL MELALUI PENGUJIAN ECONOMIC VALUE ADDED - Suripto Suripto (University of Merdeka Malang, 2010)
This research tested the influence of characteristics of the firms and of EVA (Eco-nomic Value Added) to stock of returns. This Research sample was company Self-100 ValueCreator of year 2001 until 2006. Result of research indicated that company size measure,profitability, capital structure (characteristics of the firms ) and EVA by stimulant had aneffect on significant to stock of returns, but by partial only characteristics company. Condi-tion of company fundamentals had an effect on significance to stock of returns. This indica-tion that investor still considered factors of fundamentals was having investment. EVA didnot have an effect on significant to stock of returns. This finding indicated that Model deter-mination of stock of returns (CAPM Irrelevant determined the level of EVA and also indicatedthat CAPM (Capital Assets Pricing Model) was not relevant in determining stock of returns inIndonesian Stock Exchange.